2006
DOI: 10.5194/angeo-24-2471-2006
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of gravity waves in the Equatorial Middle Atmosphere: results from ISRO's Middle Atmospheric Dynamics (MIDAS) program

Abstract: Abstract. Altitude profiles of temperature in the stratospheric and mesopheric region from lidar observations at NARL, Gadanki, India,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Subsequently, the gravity wave potential energy profiles are averaged to obtain the seasonal mean profile. By employing this procedure Ramkumar et al (2006) reported that the mean potential energy of gravity waves generally vary between 8 and 30 J/kg in the stratosphere and goes to a maximum of 35 J/kg in the 50-60 km region. Over Gadanki, there were a total of 109 SABER temperature profiles in the 5°9 10°g rid for the winter of 2004-2005.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, the gravity wave potential energy profiles are averaged to obtain the seasonal mean profile. By employing this procedure Ramkumar et al (2006) reported that the mean potential energy of gravity waves generally vary between 8 and 30 J/kg in the stratosphere and goes to a maximum of 35 J/kg in the 50-60 km region. Over Gadanki, there were a total of 109 SABER temperature profiles in the 5°9 10°g rid for the winter of 2004-2005.…”
Section: Resultsmentioning
confidence: 97%
“…The data are obtained as a part of ISRO's 5 year long Middle Atmospheric Dynamics (MIDAS) campaign. The details of the MIDAS programme along with their objectives can be found in detail in Ramkumar et al (2006). Inter comparison of the estimated gravity wave potential energy height profiles is carried out between LIDAR and SABER.…”
Section: Lidar Observations Over Gadankimentioning
confidence: 99%
“…Owing to the importance of this enigmatic region during the past few decades, various ground-and space-based investigations have been carried out to improve the overall understanding of the physical, chemical and dynamical processes (e.g. Ramkumar et al 2006 and references therein). Many unresolved scientific issues related to the middle atmospheric region still exist; hence, the middle atmospheric dynamics has been a focus of increasing scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…The fortnightly RH-200 rocket launches at Thumba yielded wind velocity profiles in the height region 20-65 km using the chaff releases (Ramkumar et al, 2006). The launch schedule during February-April 2006 was designed in order to have composite 24-h local time coverage at a time resolution of four hours.…”
Section: Observations and Data Analysismentioning
confidence: 99%